PENGARUH KEHADIRAN BIDAN TERHADAP PARTISIPASI IBU BALITA DI POSYANDU WILAYAH KERJA PUSKESMAS I SOKARAJA KABUPATEN BANYUMAS TAHUN 2012 - Fajarsari, Dyah; Utami, Laela Rizqi; ., Ratifah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
Integrated Health Center (IHC) is a forum for communication, technology transfer and public health services by and for the people that have strategic value in developing human resources early on. Utilization of health facilities such as IHC has not been optimally implemented due to the lack of public awareness, especially toddlers mother, so indispensable to the support or participation of midwife in achieving the success of the program, because people will be more motivated by the presence of midwife at the time of the activity held. This research aims to knowing the influence of the presence of a midwife to mother toddler participation in the region of IHC Puskesmas I Sokaraja Banyumas in 2012. The kind of this research in this study was observational with cross sectional approach. As research subjects is in the region of IHC I Sokaraja Banyumas in 2012. Sampling technique was done by using a proportional random sampling. Using simple regression analysis. Data collection is obtained from the IHC data report in 2012. The known research results: There was influence of the presence of a midwife to toddler mother participation in IHC Puskesmas I Sokaraja Banyumas in 2012, p < Î± = 0,00 < 0,05. The higher the frequency of the presence of midwife, the higher the mother toddler participation in IHC.Keywords : Midwife Presence, Participation Of Toddler Mother